Nanocarrier-Mediated Targeting of Tumor and Tumor Vascular Cells Improves Uptake and Penetration of Drugs into Neuroblastoma - Pastorino, Fabio; Brignole, Chiara; Loi, Monica; Di Paolo, Daniela; Di Fiore, Annarita; Perri, Patrizia; Pagnan, Gabriella; Ponzoni, Mirco (Frontiers in Oncology, 2013)
Neuroblastoma (NB) is the most common extracranial solid tumor in children, accounting for about 8% of childhood cancers. Despite aggressive treatment, patients suffering from high-risk NB have very poor 5-year overall survival rate, due to relapsed and/or treatment-resistant tumors. A further increase in therapeutic dose intensity is not feasible, because it will lead to prohibitive short-term and long-term toxicities. New approaches with targeted therapies may improve efficacy and decrease toxicity. The use of drug delivery systems allows site specific delivery of higher payload of active agents associated with lower systemic toxicity compared to the use of conventional (‘free’) drugs. The possibility of imparting selectivity to the carriers to the cancer foci through the use of a targeting moiety (e.g., a peptide or an antibody) further enhances drug efficacy and safety. We have recently developed two strategies for increasing local concentration of anticancer agents, such as CpG-containing oligonucleotides (ODNs), small interfering RNAs (siRNAs) and chemotherapeutics in NB. For doing that, we have used the monoclonal antibody anti-disialoganglioside (GD2), able to specifically recognize the NB tumor and the peptides containing NGR and CPRECES motifs, that selectively bind to the aminopeptidase N (APN)-expressing endothelial and the aminopeptidase A (APA)- expressing perivascular tumor cells, respectively. The review will focus on the use of tumor- and tumor vasculature -targeted nanocarriers to improve tumor targeting, uptake and penetration of drugs in preclinical models of human neuroblastoma.